Coating of titanium plate by photocurable azidophenyl chitosan derivative for application to implants. Issue 6 (23rd October 2012) - Seo, Si Yoong; Park, Shin Hye; Lee, Hyung Jae; Heo, Yun; Na, Ha Na; Kim, Kwang Il; Han, Jae Hong; Ito, Yoshihiro; Son, Tae Il
Abstract Titanium (Ti) is widely used as an implant material. There are various kinds of Ti surface modification methods to facilitate effective osseointegration. In this study, UV‐curable azido‐LMC (azidophenyl low molecular weight chitosan) was used to modify the Ti surface. Here we suggest a novel Ti coating material that confers complex, diverse improvements to the Ti surface through a simple process. First, a cytotoxicity test of azido‐LMC against osteoblast MG‐63 was performed. The curing ratio dependent on UV irradiation time and concentration was determined by a comparison of weight. A 5% azido‐LMC solution, which showed a wide curing ratio range, was used to investigate the surface properties. The contact angle value was measured to compare hydrophilicity, and osteoblast MG‐63 cells were cultured on the coating surface. The Bradford assay was used to assess the protein immobilization capability. Hydroxyapatite, which has a beneficial influence on osseointegration, was included on the coating surface and observed by scanning electron microscopy. Surface roughness was measured by atomic force microscopy. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013